Efektivitas Pemberian Probiotik Bifidobacterium longum Terhadap Pertumbuhan Pseudomonas aeruginosa Pada Mencit (Mus musculus) - Adrian, Adrian; Wiriansya, Edward Pandu; Ikram, Dzul; Muchtar, Amrizal; Anshary, Suci Noviyanah; Karim, Marzelina; Fazdlurrahman, Fazdlurrahman; Ahmad, Izhar Fitrah; Faisal, M. Fathir; Usman, Muh. Muflih; Ilham, Muhammad (Jurnal Biomedika dan Kesehatan, 2025)
Background Pseudomonas aeruginosa is an opportunistic, Gram-negative bacterium that can cause infections both acutely and chronically. Antibiotics are essential for treating acute bacterial infections. The use of probiotics is one effort to reduce the number of resistant antibiotics. One of the probiotics derived from microorganisms is Bifidobacterium longum. This study was conducted to determine the effectiveness of Bifidobacterium longum on the growth of Pseudomonas aeruginosa in mice (Mus musculus). Methods This study was conducted using the True Experimental Post-test method. The population used was 3- to 4-month-old mice, with a body weight of 20 to 40 grams, as determined by the Federer formula. The mice were fed standard food and given sterile distilled water. A total of 30 mice were tested and divided into five treatment groups. The test carried out is a test of the distribution of the number of colonies. Results Of the five groups studied, the administration of Bifidobacterium longum combined with the antibiotic ceftriaxone in the probiotic intervention group yielded an effective result (p < 0.05), as did the group that received only Bifidobacterium longum probiotics (p < 0.05). at the same time, the other group did not show an effective result (p >0.05). Conclusions Based on the study, it was explained that the administration of Bifidobacterium longum was effective as a supportive and curative group, but not as a preventive measure against the growth of Pseudomonas aeruginosa in mice.